The improvement of students’ scientific literacy through problem-based STEM learning on static fluid - P Parno; Lia Yuliati; Lestari Widodo; Nuril Munfaridah (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The purpose of this study was to know students’ scientific literacy after they studied problem-based STEM learning. The study used mixed method with embedded experimental design. The instrument test of this studyconsisted of 5 essay questions to measure students’ scientific literacy with reliability Cronbach’s alpha 0.72.Other instruments used in this study were the interview guide and questionnaire. The subjects of this study were 27 students in SMAN 8 Muaro Jambi who studiedstatic fluid. The result of this study shows that there is an increasedstudents’ scientific literacy after studyingproblem-based STEM learning as shown by the higher post-test scoresin comparison with the pre-test scores. The significance of the improvement of students’ scientific literacy is shown by8.35 in t value with significant 0.0000. The interview result shows that through problem-based STEM learningthe students are easy to understand the phenomena in the daily lives. Besides, the students can interpret the data evidence and design an experiment.The improvement of students’ scientific literacy is shown by N-gain in medium category. The influence of problem based STEM learning toward students’ scientific literacy is shown by the Cohens d-effect size. It is 1.72 with high category. The students positively responded towardproblem-based STEM learningas shown by 58.2 % of the students indicated in “agree”scale and 38.3% in “strongly agree” scale.